DAMPAK SISTIM PENENTUAN KOSA KATA INDEKS PADA KARYA MONOGRAF TERHADAP TEMU BALIK INFORMASI PEMUSTAKA DI DINAS PERPUSTAKAAN DAN ARSIP KOTA JAMBI - Harys, Khatimah (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2017)
This writing aims to express about the subject analyse system that be done by librarian who has choosed the vocabulary to represent a document. This system analyse is very important because it will impact to information retrieval system. The librarian must analyse a document not only its but also its content, so that he will choose some good vocabularies. The system that had been done by the librarians of Dinas Perpustakaan dan Arsip Daerah Kota Jambi where they focused the topic of document, the uncontrolled vocobulary (bahasa alami) was not be translated in to controlled vocabulary (bahasa indeks), they didn’t think the users who use library. The weakness factors are based on ; the librarian do not understand the foreign language, they can not be indexing, they do not understand the subject analyse process. This condition will affect on the unsatisfaction of users where they will not get a document that be needed, it is not effectiveness in searching, and it is more hingher acquirement than precision.